Public entities as undertakings under competition rules - Repas, Martina (Lex localis, 2010)
This paper deals with undertakings, i.e. entities that are obliged to act in accordance with competition rules. This issue is one of the key elements for the application of competition rules. Its importance derives from severe consequences in case of breach of these rules that may give rise to fines, nullity of agreements, and in some regulations, even to criminal offences. For this purpose, the paper explains the notion of "undertaking" as understoodin the EU and Slovenian competition law systems. It deals especially with public bodies such as states, local communities, public institutes, and others that can also qualify as undertakings when they perform activities for pay in the market, and are thus obliged to follow competition rules. A review of the case law shows that many public entities have been under the Competition Authority's investigation of infringements of competition rules.
Keywords: Evropska unija; konkurenčno pravo; podjetja; Slovenija; združevanje